Active Faulting, Submarine Surface Rupture, and Seismic Migration Along the Liquiñe‐Ofqui Fault System, Patagonian Andes. Issue 9 (1st September 2020) - Villalobos, Angelo; Easton, Gabriel; Maksymowicz, Andrei; Ruiz, Sergio; Lastras, Galderic; De Pascale, Gregory P.; Agurto‐Detzel, Hans
Abstract: The intra‐arc Liquiñe‐Ofqui Fault System (LOFS) is an active transpressive fault zone located in the Patagonian Andes of Chile. In 2007, a seismic sequence occurred in the Aysén Fjord region of Chilean Patagonia along the LOFS, with a Mw 6.2 main earthquake that triggered dozens of landslides, some of which induced tsunami waves that caused severe damage and casualties. Through the analysis of high‐resolution seismic reflection and bathymetric data, we identify six submarine faults cutting the Late Quaternary postglacial sedimentary infill of the fjord. The most conspicuous are the dextral‐normal NE‐SW striking Quitralco fault (QF) and the N‐S striking strike‐slip Río Cuervo (RCF) and Punta Cola faults (PCF). Our paleoseismological analysis reveals at least seven paleolandslide events buried in the fjord sediments that were triggered by local paleoearthquakes, which occurred since local ice sheet retreat, that is, circa 12 kyr. By combining tectonic observations with local seismicity data, we propose a seismotectonic model for the evolution of the 2007 seismic sequence where three structures were progressively activated from the depth toward the upper continental crust, causing surface rupture along the PCF and with earthquakes, suggesting only partial ruptures along other faults. Because the other faults did not rupture to the seafloor they remain important sources of seismic hazard. Thus, the last seismic sequence was a consequence of a stress transfer from the lower‐ductile toward the upper‐brittle continental crust, close to the triple junction of the Nazca, South American, and Antarctica Plates. Our results emphasize on the potential synergies between multiple geological and geophysical methods to assess complex events. Plain Language Summary: When crustal faults rupture, the energy released is the earthquakes we feel at the surface of the Earth. Recent studies along strike‐slip faults demonstrate that these phenomena are often not only related to a single fault but instead take place along several faults like was seen in the 2016 Kaikoura earthquake in New Zealand. Using novel high‐resolution seismic reflection imagery and bathymetric data together with the reanalysis of local seismicity, we show (i) multiple active faults in the Aysén Fjord area along the Liquiñe‐Ofqui Fault System in the Patagonian Andes; (ii) several of these faults were activated during the last 2007 seismic sequence and one of them (the Punta Cola fault), ruptured to the surface causing a Mw 6.2 earthquake that generated massive landslides and local tsunami; and (iii) mapping of similar landslides in the fjord sediments demonstrates similar events occurred at least seven times since the last ice sheet retreat in the area, that is, in the last 12, 000 yr. This demonstrates the necessity for including the possibility of complex ruptures involving multiple faults regarding seismic hazard assessment along crustal faults, especially for faults near populated areas. Key Points: High‐resolution seismic reflection and bathymetric data reveal seafloor rupture and multiple faults cutting postglacial fjord sediments Four‐dimensional seismotectonic model shows that the 2007 Aysén Seismic Sequence resulted in multiple faults activation and surface rupture Seven paleoearthquakes similar to 2007 main event caused landslides and conspicuous deformation of the fjord's seafloor, during the last 12 kyr